2019
DOI: 10.1007/s12178-019-09594-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Forward Head Posture and Neck Pain: a Systematic Review and Meta-Analysis

Abstract: Purpose of Review Forward head posture (FHP) is the most common cervical postural fault in the sagittal plane that is found with different severity levels in almost all populations. Despite claims that FHP may be related to neck pain, this relation seems to be controversial. Thus, our purpose is to determine whether FHP differs between asymptomatic subjects and those with neck pain and to investigate if there is a relationship between head posture and neck pain. Recent Findings A total of 15 cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 58 publications
2
85
1
7
Order By: Relevance
“…Workers with a smaller distance between the keyboard and the edge of the desk tended to suffer form chronic NSP, indicating that less or no support for the forearms might contribute to chronic NSP. Thirdly, bending the neck forward and twisting the neck for long periods of time were associated with chronic NSP, similar with the results of a systematic review and meta-analysis 51 which reported that adults with neck pain was correlated with increased forward head posture when compared to asymptomatic adults. At same time we also need to note that bending the neck forward and twisting the neck for long periods of time might be associated with pain measures 51 and need to be identified for chronic NSP in the future in cohort studies although correlation between them was found in the study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Workers with a smaller distance between the keyboard and the edge of the desk tended to suffer form chronic NSP, indicating that less or no support for the forearms might contribute to chronic NSP. Thirdly, bending the neck forward and twisting the neck for long periods of time were associated with chronic NSP, similar with the results of a systematic review and meta-analysis 51 which reported that adults with neck pain was correlated with increased forward head posture when compared to asymptomatic adults. At same time we also need to note that bending the neck forward and twisting the neck for long periods of time might be associated with pain measures 51 and need to be identified for chronic NSP in the future in cohort studies although correlation between them was found in the study.…”
Section: Discussionsupporting
confidence: 82%
“…Thirdly, bending the neck forward and twisting the neck for long periods of time were associated with chronic NSP, similar with the results of a systematic review and meta-analysis 51 which reported that adults with neck pain was correlated with increased forward head posture when compared to asymptomatic adults. At same time we also need to note that bending the neck forward and twisting the neck for long periods of time might be associated with pain measures 51 and need to be identified for chronic NSP in the future in cohort studies although correlation between them was found in the study. Fourthly, our study showed that hospital workers with temporary/contract employment status were more prone to suffering from chronic NSP than those with permanent employment status.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that individuals with neck problems have a greater tendency to make adaptations in the head and neck, and a significant relationship has been found between FHP and neck pain [31,38]. In a study that compared patients with severe chronic neck pain with subjects with no neck pain, those with chronic pain were found to have a reduced ability to maintain an upright neutral posture at a computer [31].…”
Section: Discussionmentioning
confidence: 99%
“…The term cervicogenic headache (CGH) refers to a headache caused by a dysfunction in the cervical spine and its osseous, disc and/or soft tissue components, which is usually accompanied by cervical pain [ 1 ] and one-sided pain referred to the head [ 2 ]. Cervical pain has been proposed as a possible trigger for headache [ 3 ] because of the convergence in the trigeminal nucleus caudalis [ 4 ]. Cervical pain is one of the most common musculoskeletal complaints in the adult population, with an annual incidence ranging from 10.4% to 21.3% and a prevalence of up to 86.8% in developed countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that cranio-cervical pain is related to posture alterations [ 10 ], forward head posture (FHP) being one of the most investigated, which is characterized by a decreased cranio-cervical angle (CCA) [ 11 ] leading to an extension of the occipital and upper cervical spine and a flexion of the medium-lower cervical spine [ 3 ]. This posture induces a lengthening of the cervical extensors and occipital flexors muscles, and a shortening of the cervical flexor muscles and suboccipital muscles [ 12 ], which are the most shortened [ 13 ].…”
Section: Introductionmentioning
confidence: 99%